2015
DOI: 10.1039/c5ra00452g
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the microwave electric or magnetic field in the synthesis of monometallic and bimetallic nanoparticles

Abstract: The wet synthesis of mono-disperse Ag, Ag-Ni, and Pd-Ag nanoparticles has been performed employing glycol solutions containing [Ag(NH 3 ) 2 ]+ and a second metal cation Mn + (M ¼ Ag, Na, Al, Ni or Pd) under microwave irradiation in a predominately electric (E-) or a predominately magnetic (H-) field. No specific effects of the microwave E-field and H-field on the rate of product formation have been observed. But the synthesis of Ag-Ni alloy particles in the E-field and the H-field resulted in products with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The TM 110 mode with the maximum magnetic field on the cylindrical center axis was used as the MW irradiation method. Although magnetic-field heating has been used in solid-phase syntheses or metal heating, there are a few examples of chemical syntheses of solution systems using a magnetic-field-concentrated mode. Therefore, the characteristics of solutions heated using the present apparatus were investigated for a conventional tubular-type reactor. Then, continuous syntheses of metal nanoparticles were conducted as chemical reaction examples in this SFprocess.…”
Section: Introductionmentioning
confidence: 99%
“…The TM 110 mode with the maximum magnetic field on the cylindrical center axis was used as the MW irradiation method. Although magnetic-field heating has been used in solid-phase syntheses or metal heating, there are a few examples of chemical syntheses of solution systems using a magnetic-field-concentrated mode. Therefore, the characteristics of solutions heated using the present apparatus were investigated for a conventional tubular-type reactor. Then, continuous syntheses of metal nanoparticles were conducted as chemical reaction examples in this SFprocess.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, microwave (MW) irradiation is one of the most sophisticated methods for the preparation of nanoparticles with controlled size and shape. In the past decade, there has been increasing attention in the use of MW heating instead of conventional heating in various kinds of monometallic and bimetallic nanoparticle syntheses, because MW heating has been shown to reduce dramatically the reaction times and to enhance the purity of the nanoparticles produced. For example, Bensebaa et al used MW heating to produce Pt/Ru bimetallic nanoparticles in ethylene glycol (EG) solution dissolving PVP and demonstrated that microwave preparation parameters are linked to surface composition and structure.…”
Section: Introductionmentioning
confidence: 99%
“…Interior and exterior of the materials are heated at the same time. And the materials are heated quickly and uniform [7][8][9]. In this work, we used microwave reactor to synthesis Ag/Cu bimetallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%